Comprehensive FGFR3 alteration-related transcriptomic characterization is involved in immune infiltration and correlated with prognosis and immunotherapy response of bladder cancer - Xu, Ting; Xu, Weizhang; Zheng, Yuxiao; Li, Xiao; Cai, Hongzhou; Xu, Zicheng; Zou, Qing; Yu, Bin (Frontiers in Immunology, 2022)
Background: Bladder cancer (BC) threatens the health of human beings worldwide. As an actionable biomarker, fibroblast growth factor receptor 3 (FGFR3) alterations have been revealed as a vital biomarker and associated with favorable outcomes in BC. However, the comprehensive relationship between the FGFR3 alteration associated gene expression profile and the prognosis of BC remains ambiguous. Materials and Methods: Genomic alteration profile, gene expression data and related clinical information of BC patients were downloaded from The Cancer Genomics database (TCGA), as a training cohort. The Weighted Gene Co-expression Network Analysis (WGCNA) together with univariate, multivariate, and least absolute shrinkage and selection operator (LASSO) Cox regression analyses identified a FGFR3 alteration-related genes (FARGs) signature and a FARGs-based nomogram. Results: There were a total of eleven genes (CERCAM, TPST1, OSBPL10, EMP1, CYTH3, NCRNA00201, PCDH10, GAP43, COLQ, DGKB, and SETBP1) involved in FARGs signature, which divided TCGA-BC patients into high- and low- risk groups. The Kaplan-Meier (K-M) curve analysis demonstrated that BC patients in low-risk group have superior overall survival (OS) than those in high-risk group. Moreover, the FARGs signature even could distinguish patients with different neoplasm disease stages, notably whether patients presented with muscle invasive phenotype. Of note, FARGs signature was found to be an only independent prognostic factor, and subsequently, a FARGs-based prognostic nomogram was constructed with better ability of prognosis prediction. Underlying the FARGs signature, multiple kinds of metabolism- and immune-related signaling pathways were enriched. Genomic alteration enrichment further identified that FGFR3 alterations, especially p.Ser249Cys were more prevalent in the low-risk group. Additionally, FARGs prognostic score was positively correlated with ESTIMATE and TIDE scores, and low-risk group had abundant enrichment of plasma B cell, CD8+ T cells, CD4+ naive T cells, helper follicular T cell, implying that patients in low-risk group were likely to make significant responses to immunotherapy, which was further validated in IMvigor210 cohort as there was a significantly higher response rate among patients with lower FARGs prognostic scores. Conclusion: The novel established FARGs signature performed well in prognosis prediction and was also correlated with immunotherapy treatment responses, which had great potential in future clinical applications.